The Effect of Different Tillage Methods and Nitrogen Chemical Fertilizer on Quantitative and Qualitative Characteristics of Corn - Reza Imani; Morteza Samdeliri; Amirabbas Mousavi Mirkalaei (International Journal of Analytical Chemistry)
Selection of suitable tillage and application of optimal nitrogen fertilizer are essential to achieve optimal efficiency in crop management. In order to investigate the effect of tillage and nitrogen fertilizer on photosynthetic pigments and quantitative and qualitative traits of corn grain, an experiment was conducted in the research farm of Islamic Azad University, Chalous Branch, Mazandaran Province, Iran, in 2016 and 2017. Experimental factors were tillage at three levels, including no-tillage (NT), conservation tillage (MT), and conventional tillage (CT) in the main plot, and nitrogen fertilizer at four levels (no nitrogen fertilizer application and 33, 66, and 100% of the recommended amount of nitrogen fertilizer) in a subplot. The results showed that, in tillage treatments, increasing nitrogen fertilizer application increased photosynthetic pigments. Carotenoids and chlorophyll b were not significantly different in CT and MT treatments. Nitrogen and grain protein, yield components, and biological yield increased with the increasing use of recommended nitrogen fertilizer. The highest grain and biological yields in MT in the second year were observed at 11633.15 and 16644.16 kg·ha1, respectively. Grain and biological yield in the second year than the first year were further increased in NT and MT treatments compared to CT. Yield in MT and NT treatments improves over time. Due to the time limit in land preparation in the study area, the use of MT with 100 and 66% of the recommended nitrogen fertilizer can replace CT in the area.